STRATEGI DAKWAH RASULULLAH DI MADINAH - Mahmuddin Mahmuddin (Jurnal Dakwah Tabligh, 2020)
This study discusses the Prophet's preaching strategy in Medina. The issue is then broken down into research questions, namely: what are the steps of the Prophet's propaganda strategy in Medina? The object of this research is the steps of the propaganda strategy of the Prophet practised in Medina. The method used is using the method of documentation and analysis of historical texts. The results showed that the Messenger of Allāh do in carrying out da'wah had used the tactics and preaching strategy steps in Medina, starting from Mecca to his missionary journey in Medina. The implementation of the Prophet's preaching strategy steps in the form of preaching planning strategy, preaching organization strategy, preaching implementation strategy and preaching and controlling strategy and evaluation, all of which have been implemented in a strict and structured manner.